Chemical and nutritional characterization of raw and thermal-treated flours of Mesquite (Prosopis laevigata) pods and their residual brans - Luis Díaz-Batalla; Juan P. Hernández-Uribe; Alma D. Román-Gutiérrez; Raquel Cariño-Cortés; Javier Castro-Rosas; Alejandro Téllez-Jurado; Carlos A. Gómez-Aldapa (CyTA - Journal of Food, 2018)
Species of the genus Prosopis were a major staple food in Aridoamerica before the arrival of Europeans. In the present work, chemical and nutritional properties of Prosopis laevigata pods were described. The composition in weight of pods of P. laevigata was 44% mesocarp, 35% endocarp, and 21% exocarp. Sugars, including sucrose, glucose, fructose, and xylose, were important components of pods, reaching a total sugars content of 447 g/kg in mesocarp flour. Considering the FAO-recommended amino-acid scoring patterns for humans older than 3 years, high values of Lys and sulfur-containing amino acids were found in flours. Thermal treatment of flours increases significantly the phenolic compounds content and free-radical scavenging capacity, an effect associated with the generation of Maillard reaction products. Flours of mesquite pods are a good source of phenolic compounds, with significantly higher free-radical scavenging capacity than soybean and common bean.